TXRF analysis of metals in oral fluids of patients with dental implants - Abraham, Jose A (2014)
Corrosion of metals in implanted biomaterials lifetime is expected to occur. Nowadays, medical implants have good biocompatibility, present proper mechanical properties, and promote tissue regeneration; nevertheless, corrosion will eventually happen. Biological fluids are rich in chemically active ions; hence, electrochemical processes appear on the surface of the metal immediately after implantation. In order to evaluate corrosion resistance of metal implants, several studies have been carried out in artificial environments, but their results have not been always directly correlated to living systems. This work presents an indirect study of corrosion of dental implants by analyzing changes of elemental concentration of metals in oral fluids. It will also contribute to the knowledge of implant corrosion in relation to its biological environment. Degradation of the implant surface releases material to the medium, which, depending on the concentrations, can represent toxic risk, organic malfunction, pain, rejection, and so on. In order to evaluate this process, the concentrations of representative metals such as Ti, Al, and V in saliva and gingival fluids were analyzed by means of total reflection of X-rays fluorescence analysis using synchrotron radiation. The results obtained here show that Ti-ions present a different behavior in the oral fluids, revealing higher concentrations in gingival crevice fluid than in saliva. On the other hand, V and Al have not shown significant differences from normal levels in the oral fluids. Metal release is discussed under mechanical and chemical considerations, taking into account the oral environment of the implant.